Robust strategies of climate change mitigation in interacting energy, economy and land use systems. Issue 5 (21st November 2016) - Leimbach, Marian; Labriet, Maryse; Bonsch, Markus; Dietrich, Jan Philipp; Kanudia, Amit; Mouratiadou, Ioanna; Popp, Alexander; Klein, David
Abstract : Purpose: Bioenergy is a key component of climate change mitigation strategies aiming at low stabilization. Its versatility and capacity to generate negative emissions when combined with carbon capture and storage add degrees of freedom to the timing of emission reductions. This paper aims to explore the robustness of a bioenergy-based mitigation strategy by addressing several dimensions of uncertainty on biomass potential, bioenergy use and induced land use change emissions. Design/methodology/approach: Different mitigation scenarios were explored by two different energy-economy optimization models coupled to the same land use model, which provides a common basis for the second generation bioenergy dynamics in the two energy-economy models. Findings: Using bioenergy is found to be a robust mitigation strategy as demonstrated by high biomass shares in primary energy demand in both models and in all mitigation scenarios. Practical implications: A variety of possible storylines about future uses of biomass exist. The comparison of the technology choices preferred by the applied models helps understand how future emission reductions can be achieved under alternative storylines. Originality/value: The presented comparison-based assessment goes beyond other comparison studies because both energy-economy models are coupled to the same land use model.